Пошаговое объяснение:
у=х^2 -> у=(х+2)^2 (на 2 влево)
у=х^2 -> у=-х^2+1 (на 1 вверх)
у=х^2 -> у=(х-3)^2 (на 3 вправо)
у=х^2 -> у=-(х-1)^2-3 (на 1 вправо и на 3 вниз)
у=х^2 -> у=х^2-2 (на 2 вниз)
у=х^2 -> у=у=(х+2)^2+1 (на 2 влево и на 1 вверх)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
у=х^2 -> у=(х+2)^2 (на 2 влево)
у=х^2 -> у=-х^2+1 (на 1 вверх)
у=х^2 -> у=(х-3)^2 (на 3 вправо)
у=х^2 -> у=-(х-1)^2-3 (на 1 вправо и на 3 вниз)
у=х^2 -> у=х^2-2 (на 2 вниз)
у=х^2 -> у=у=(х+2)^2+1 (на 2 влево и на 1 вверх)